Mutual versus stock insurers: Fair premium, capital, and solvency - Christian Laux; Alexander Muermann (Goethe University Frankfurt, Center for Financial Studies (CFS), 2006)
Mutual insurance companies and stock insurance companies are different forms of organized risk sharing: policyholders and owners are two distinct groups in a stock insurer, while they are one and the same in a mutual. This distinction is relevant to raising capital, selling policies, and sharing risk in the presence of financial distress. Up-front capital is necessary for a stock insurer to offer insurance at a fair premium, but not for a mutual. In the presence of an ownermanager conflict, holding capital is costly. Free-rider and commitment problems limit the degree of capitalization that a stock insurer can obtain. The mutual form, by tying sales of policies to the provision of capital, can overcome these problems at the potential cost of less diversified owners.
urn:nbn:de:hebis:30-38003
Keywords: G22; G32; 330; Ownership Structure; Insurance; Qwner-Manager Conflict; Capital; Default; Versicherung; Privatversicherung; Eigentümerstruktur; Versicherungsprämie; Eigenkapital; Betriebliche Liquidität; Theorie